Towards systemic sclerosis and away from primary biliary cirrhosis: the case of PTPN22 - Smyk, Daniel S. (Auto Immun Highlights, 2011)
Primary biliary cirrhosis (PBC) is a chronic cholestatic liver disease characterized by immune-mediated destruction of the small and medium size intrahepatic bile ducts. PBC patients often have concomitant autoimmune diseases, which are most often autoimmune thyroid disease, as well as Sicca syndrome. Occasionally, some PBC patients will also have systemic sclerosis of the limited cutaneous type (lcSSc). Conversely, up to one-fourth of SSc patients are positive for antimitochondrial antibody, the serologic hallmark of PBC. It is also common for SSc patients to have concomitant autoimmune disease, which may include PBC in rare cases. This has led to speculation of shared environmental and/or genetic factors, which lead to the development of PBC in SSc patients and vice versa. Recent genetic studies have revealed associations with several genes in both SSc and PBC. PTPN22 is one gene that has been associated with SSc, but not with PBC. It may be argued that some SSc patients with a particular genotype, which shares genes found in both conditions may develop PBC. Likewise, particular genes such as PTPN22 may infer susceptibility to SSc alone. The presence of PTPN22 may also contribute to the development of SSc in PBC patients. The lack of a large number of overlapping genes may, in part, explain the relative rarity of PBC with SSc and vice versa. This review will examine the literature surrounding the genetic associations of PBC and SSc, and the role of PTPN22 in particular.